Itraconazole inhibits the Wnt/β-catenin signaling pathway to induce tumor-associated macrophages polarization to enhance the efficacy of immunotherapy in endometrial cancer - Guan, Xin; Han, Lu (Frontiers in Oncology, 2025)
BackgroundEndometrial cancer (EC) is a common gynecologic malignancy with limited treatment options. This study aimed to evaluate the potential of itraconazole (ITZ), a widely used antifungal drug, as an anti-tumor agent and an adjuvant to immunotherapy for EC.MethodsThe effects of ITZ on Ishikawa cells were assessed using proliferation assays, apoptosis assays, and invasion assays. The combination of ITZ and immune checkpoint inhibitors (ICIs) was evaluated to determine their synergistic effects on tumor invasion. Tumor-associated macrophages (TAMs) polarization and cytokine levels were analyzed by flow cytometry and enzyme linked immunosorbent assay (ELISA). Western blotting and Real-time reverse transcription polymerase chain reaction (RT-PCR) were used to investigate the impact of ITZ on the Wnt/β-catenin signaling pathway. Finally, in vivo experiments were conducted using a mice tumor model to validate the anti-tumor effects of ITZ and its combination with ICIs.ResultsITZ inhibits Ishikawa cells proliferation and invasion through apoptosis induction. When combined with ICIs, ITZ significantly enhanced the inhibition of tumor invasion, an effect associated with TAMs polarization. ITZ increased IFN-γ secretion, reduced IL-10 levels, and promoted TAMs polarization from the M2 to the M1 phenotype. Mechanistically, ITZ downregulated Wnt-3a and β-catenin expression while upregulating Axin-1, thereby suppressing Wnt/β-catenin signaling in TAMs. In vivo, ITZ and ICIs synergistically reduced tumor volume and weight, shifted TAMs polarization toward the M1 phenotype, and suppressed Wnt/β-catenin signaling.ConclusionsITZ demonstrated robust anti-tumor activity against EC by inhibiting Ishikawa cells proliferation, invasion, and enhancing the efficacy of ICIs. Through its dual role in directly targeting tumor cells and modulating the tumor microenvironment, ITZ shows promise as a multitargeted therapeutic agent and a valuable adjuvant to immunotherapy for EC.